The preparation and morphology of biphasic calcium phosphate ceramics - P. Saiwanich (2018)
In this work, thepreparation and morphology of biphasic calcium phosphate (BCP) have been studied. The biphasic calcium phosphate(BCP) ceramics were prepared by mixing between hydroxyapatite (HA) and Beta-tricalcium phosphate (β-TCP) powder by ball milling technique with different ratios (100:0, 80:20, 60:40, 50:50, 40:60, 20:80 and 0:100). After that the mixtures were forming by Gel casting method and then sintered at 1200°C, respectively. The phase formation of the biphasic calcium phosphateceramics were studied by X-ray diffraction (XRD) and their ceramic microstructure, shrinkage and density were investigated. © (2012) Trans Tech Publications.